AN ATTEMPT TO IMPROVE TEACHERS' COMPETENCE IN DEVELOPING LESSON PLANS (RPP) THROUGH WORKSHOPS AT SDN 012 RUMBAI JAYA - Hamsah Hamsah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of teachers’ competence in developing lesson plans (RPP) through workshops. Lesson Plan is a teacher's teaching tool in the classroom. A teacher must be able to plan, create a quality teaching and learning process, and assess and evaluate learning outcomes. Workshops are a part of the investments in human resources to improve work capabilities and skills in improving employee performance. The research in this paper is a School Action Research (PTS) using the research design model of Kemmis and Mc. Taggart. The research was conducted at SDN 012 Rumbai Jaya. The research subjects involved 16 teachers. Two cycles indicate the results of the teacher's competence and development increased significantly. In the first cycle, four teachers were very active category with a percentage of 25% while in the second cycle, nine teachers were very active category with a percentage of 56.25%. Based on the quality of developing lesson plans, there is a significant improvement from cycle I to cycle II with a percentage of 50%. Thus, the teacher's competence has increased in compiling and developing Lesson Plans (RPP) through workshops at SDN 012 Rumbai Jaya.